2017
DOI: 10.7754/clin.lab.2016.161032
|View full text |Cite
|
Sign up to set email alerts
|

Turbidimetric Determination of Fecal Calprotectin Using Two Table Top Chemistry Analyzers: Mindray BS-200E and Cobas® c111

Abstract: Running the BÜHLMANN fCAL® turbo on Mindray BS-200E or cobas® c111 chemistry analyzers can provide rapid test results without exposing large routine chemistry analyzers to stool samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Bühlmann do provide validation data for the fCAL turbo assay on the Indiko Clinical Chemistry analyser (ThermoFisher Scientific, Massachusetts, USA), which is the same hardware as the Optilite, but marketed by ThermoFisher Scientific rather than Binding Site. The verification data obtained here compares well to those provided by Bühlmann on the Indiko and other published validation studies for the fCAL turbo assay on several chemistry platforms [ 3 , 7 , [13] , [14] , [15] ]. Although interference studies were not specifically investigated in this study, sample comparison was acceptable for all samples analysed, and previous reports did not identify any significant interference from a variety of drugs and other compounds with the fCAL turbo assay [ 3 ].…”
Section: Discussionsupporting
confidence: 84%
“…Bühlmann do provide validation data for the fCAL turbo assay on the Indiko Clinical Chemistry analyser (ThermoFisher Scientific, Massachusetts, USA), which is the same hardware as the Optilite, but marketed by ThermoFisher Scientific rather than Binding Site. The verification data obtained here compares well to those provided by Bühlmann on the Indiko and other published validation studies for the fCAL turbo assay on several chemistry platforms [ 3 , 7 , [13] , [14] , [15] ]. Although interference studies were not specifically investigated in this study, sample comparison was acceptable for all samples analysed, and previous reports did not identify any significant interference from a variety of drugs and other compounds with the fCAL turbo assay [ 3 ].…”
Section: Discussionsupporting
confidence: 84%
“…In clinical practice, the fC enzyme‐linked immunosorbent assay (ELISA) remains the most often applied method for the quantification of fC. The PETIA which was used in our study, was shown to be equal compared to ELISA in several studies 39–41 …”
Section: Discussionmentioning
confidence: 68%
“…Automated ELISA tests are currently available allowing to analyze the samples at any time, even individually. Importantly, the diagnostic accuracy of these tests is equivalent to the traditional ELISA method 33–40 . Recently, point of care rapid tests and home tests have been developed.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the diagnostic accuracy of these tests is equivalent to the traditional ELISA method. [33][34][35][36][37][38][39][40] Recently, point of care rapid tests and home tests have been developed. POC tests use specific lateral flow immunoassays.…”
Section: Statementmentioning
confidence: 99%